Potato seed dressing with Pseudomonas aeruginosa strain RZ9 enhances yield and reduces black scurf - MRABET, Moncef; ELKAHOUI, Salem; TARHOUNI, Belhassen; DJEBALI, Naceur (Phytopathologia Mediterranea, 2015)
A rhizospheric strain RZ9 of Pseudomonas aeruginosa was assessed for in-vitro growth inhibition of Rhizoctonia solani and effectiveness to control black scurf on potatoes (Solanum tuberosum L.) of the cultivars Spunta and Nicola, in greenhouse and field experiments. The strain RZ9 inhibited R. solani mycelial growth by more than 60% and completely inhibited the germination of sclerotia from infested potato tubers in in-vitro tests. In greenhouse assays, seed potato treatment with RZ9 cell suspension increased stem length, decreased the relative weight of infected potato tubers (by 67%), and increased the potato yield (by 16%) compared to pathogen-inoculated plants for both potato cultivars. In field trials conducted on sandy soils during 2012 and 2013, strain RZ9 reduced black scurf incidence and increased potato yield by an average of 5.3 t ha-1 for ′Spunta′ and 5 t ha-1 for ′Nicola′. This study showed that the selected strain of P. aeruginosa is an efficient bacterium for enhancing yield and reducing black scurf of field-grown potatoes.